2013
DOI: 10.1007/s10693-013-0176-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Lending and Credit Quality

Abstract: We analyze if the relationship lending reduces the borrower's probability of borrowers' default and if this beneficial effect operates also for those borrowers who are more exposed to the economic downturn. By using unique, matched data of 43,000 firms and their lending institutions between 2008 and 2010, we document that the probability that a firm becomes distressed decreases when the creditor concentration is high and the duration of bank-firm relationships is long. While these results seem to support the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 51 publications
0
43
0
Order By: Relevance
“…Within this situation, banks could mitigate information asymmetries in the credit market through monitoring activities, but the incentive to acquire and assess the creditworthiness of the borrower is low in the case of multiple lending, as the cost would be borne by only one lender, whereas the benefits would be spread among all of them. Banks can resolve this information asymmetry by implementing closer relationships with firms, especially smaller ones (Ramakrishnan and Thakor, ; Fama, ; Rajan, ; Fiordelisi et al ., ).…”
Section: Theoretical Foundationsmentioning
confidence: 97%
See 2 more Smart Citations
“…Within this situation, banks could mitigate information asymmetries in the credit market through monitoring activities, but the incentive to acquire and assess the creditworthiness of the borrower is low in the case of multiple lending, as the cost would be borne by only one lender, whereas the benefits would be spread among all of them. Banks can resolve this information asymmetry by implementing closer relationships with firms, especially smaller ones (Ramakrishnan and Thakor, ; Fama, ; Rajan, ; Fiordelisi et al ., ).…”
Section: Theoretical Foundationsmentioning
confidence: 97%
“…As previously mentioned, relationship lending is based on the availability of private or soft information, which allows the bank to identify the most appropriate contractual structure to be proposed to the firm in order to extend credit. This kind of knowledge is generated by a privileged, collaborative and repeated lending relationship with the firm (Cotugno et al ., ; Fiordelisi et al ., ). However, soft information cannot be measured directly, therefore, in the literature it was initially related to the size of the firm and/or the bank.…”
Section: Relationship‐specific Determinantsmentioning
confidence: 97%
See 1 more Smart Citation
“…Organizational distance has been measured using physical distance in kilometers (km) between locations of a bank's headquarters and capital of province where a firm is located such that bank-firm organizational distance was measured using inverse of distance [33]. Similarly, organizational distance has been measured using distance in kilometer between province of firm and bank headquarters [82]. In contrast, it has been shown that organizational distance can be measured based on whether two organizations belong to same corporate group, such that a binary variable is assigned the value 1 when two firms are owned by same corporate group, or 0 otherwise [38].…”
Section: Measurements For Organizational Proximitymentioning
confidence: 99%
“…The amount of fixed assets divided by total assets (FIXED) is considered a proxy for collateralizable assets, and CREDITRATIO represents the ratio of credit drawn and credit granted related to firm i in year t . This ratio is an inverse measure of credit availability and is typically used by banks to assess firm fragility: the higher the ratio is, the greater the likelihood that the firm is liquidity constrained (Buttiglione and Ferri ; Bonaccorsi di Patti, Gaiotti, and Lotti ; Fiordelisi, Monferrà, and Sampagnaro ). Then, we create OVERDRAWN i,t , which represents a binary variable that equals 1 if the ratio is greater than or equal to 1, and 0 otherwise.…”
Section: Additional Evidence: Effects Of Bank–firm Interactionmentioning
confidence: 99%